BAKSO SINTETIS BAKSO SINTETIS DARI CAMPURAN GLUTEN TEMPE DENGAN PENAMBAHAN TEPUNG TAPIOKA - .,, Jariyah; H P, Sudaryati; Kurniawati, Lusiana (REKAPANGAN, 2009)
BAKSO SINTETIS BAKSO SINTETIS DARI CAMPURAN GLUTEN TEMPE DENGAN PENAMBAHAN TEPUNG TAPIOKA